Traditions and plant use during pregnancy, childbirth and postpartum recovery by the Kry ethnic group in Lao PDR - de Boer Hugo J; Lamxay Vichith; Björk Lars (BMC, 2011)
Abstract Background Activities and diet during the postpartum period are culturally dictated in many Southeast Asian cultures, and a period of confinement is observed. Plants play an important role in recovery during the postpartum period in diet and traditional medicine. Little is known of the Kry, a small ethnic group whose language was recently described, concerning its traditions and use of plants during pregnancy, parturition, postpartum recovery and infant healthcare. This research aims to study those traditions and identify medicinal plant use. Methods Data were collected in the 3 different Kry villages in Khammouane province, Lao PDR, through group and individual interviews with women by female interviewers. Results A total of 49 different plant species are used in women's healthcare. Plant use is culturally different from the neighboring Brou and Saek ethnic groups. Menstruation, delivery and postpartum recovery take place in separate, purpose-built, huts and a complex system of spatial restrictions is observed. Conclusions Traditions surrounding childbirth are diverse and have been strictly observed, but are undergoing a shift towards those from neighboring ethnic groups, the Brou and Saek. Medicinal plant use to facilitate childbirth, alleviate menstruation problems, assist recovery after miscarriage, mitigate postpartum haemorrhage, aid postpartum recovery, and for use in infant care, is more common than previously reported (49 species instead of 14). The wealth of novel insights into plant use and preparation will help to understand culturally important practices such as traditional delivery, spatial taboos, confinement and dietary restrictions, and their potential in modern healthcare.